Binmas Online System V2: Effectiveness and Performance Improvement of “Bhabinkamtibmas” in Cirebon City Police Resort - Elvira Amalia Pontoh, Riza; Ghazi Saepuloh, Azhar; Putri Utami, NL Wira; Ade Maulana, Muhammad; Umari Tauhid, Duta; Dimas Wicaksono, Harris (Indonesian National Police Academy, 2024)
Digital transformation can have a significant impact on the police, because the use of information technology which is the main basis of digital transformation can enable the police to be able to analyze information faster, process larger and more accurate data, and provide more effective services to the public. To solidify the performance of maintaining public security, strengthening the performance of Bhabinkamtibmas was carried out with the launch of Binmas Online System Version 2 (BOS V2) by Baharkam Polri on May 5, 2021 which helps Bhabinkamtibmas carry out their duties. However, the use of the Binmas Online System Version 2 (BOS V2) application is still not effective and has not been able to support the implementation of Bhabinkamtibmas tasks at the Cirebon City Police Station. This study aims to describe the effectiveness of the Binmas Online System (BOS V2) application in improving the performance of Bhabinkamtibmas as well as improving the performance of Bhabinkamtibmas after the use of the Binmas Online System (BOS V2) application at Cirebon City Police. The method used in this research is qualitative. The theories and concepts used include effectiveness theory, technology acceptance theory, Bhabinkamtibmas concept, and Binmas Online System (BOS V2) concept. The results showed that based on the indicators measuring effectiveness in the theory of effectiveness, it can be concluded that the objectives of BOS V2 and Bhabinkamtibmas have not been achieved and the BOS V2 application still has a number of shortcomings in terms of features and functionality including the inability of the server to be reached, limited time for sending reports, and inconsistencies in data input.